Biomass Conversion to Fuels and Value-Added Chemicals: A Comprehensive Review of the Thermochemical Processes - Muh, Erasmus; Tabet, Fouzi; Amara, Sofiane (Current Alternative Energy, 2021)
Fossil fuels have fueled the world economy for decades. However, given their limited nature, fluctuating prices and the escalating environmental concerns, there is an urgent need to develop and valorize cheaper, cleaner and sustainable alternative energy sources to curb these challenges. Biomass represents a valid alternative to fossil fuels, especially for fuel and chemical production as it represents the only natural organic renewable resource with vast abundance. A vast array of conversion technologies is used to process biomass from one form to another, to release energy, high-value products or chemical intermediates. This paper extensively reviews the thermochemical processing of biomass to fuels and high-value chemicals, with an emphasis on the process performance, conditions, and weaknesses. Technologies with great future prospects as well as those with possible linkage to CO2 capture and sequestration are highlighted. The important chemical compositions of biomass feedstock, their conversion technologies and most importantly, the role of catalysis in their conversion to fuels, fuel additives, based chemicals, and added-value chemicals are also discussed. Special attention is given to biofuel production for transportation as this sector is responsible for the highest global greenhouse gas emissions, and has an emerging market with promising future prospects for sustainable large-scale biomass processing. The processes involved in the purification and upgrading of biomass-derived products into higher-value products are equally discussed and reviewed.
Keywords: biomass